2013
DOI: 10.1021/cs400291t
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Effect over the Biginelli Reaction under Homogeneous and Heterogeneous Catalysis

Abstract: Bronsted and Lewis acid catalysts with ionic tags under homogeneous and heterogeneous conditions have been tested to perform the Biginelli synthesis of 3,4-dihydropyrimidin-2­(1H)-one (DHPMs). Metal-containing ionic liquids were evaluated as the catalysts with reasonable results (homogeneous systems). Heterogeneous catalysts (zeolite β and H3PW12O40 supported on zeolite β) have been tested, as well, with good to excellent results. The use of a functionalized acid ionic liquid with a heteropolyacid in the anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
59
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 81 publications
4
59
0
1
Order By: Relevance
“…For instance, we have shown that BMI.InCl 4 is capable of promoting the tetrahydropyranylation of alcohols [12], in situ generation and stabilization of iminium ions [13] and to copromote the formation and stabilization of charged-intermediates during transesterification reactions [14]. We have also recently investigated iron-based ILs as catalysts for oxidation [15], reduction [16] and multicomponent reactions [17][18][19]. In this sense, we have therefore envisaged that the iron-containing ILs could also work as efficient catalysts for the styrene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have shown that BMI.InCl 4 is capable of promoting the tetrahydropyranylation of alcohols [12], in situ generation and stabilization of iminium ions [13] and to copromote the formation and stabilization of charged-intermediates during transesterification reactions [14]. We have also recently investigated iron-based ILs as catalysts for oxidation [15], reduction [16] and multicomponent reactions [17][18][19]. In this sense, we have therefore envisaged that the iron-containing ILs could also work as efficient catalysts for the styrene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, 34 a MOF scaffold was tested as the heterogeneous catalyst for the Biginelli reaction with relative success, but the tested material was already known for its instability, especially in the presence of moisture, [35][36][37] which is a highly limiting feature. Most motivated by our interest in MCRs, 38 especially in the Biginelli reaction, [39][40][41] and due to our expertise in the synthesis and application of CPs/MOFs, [42][43][44] we describe herein a successful strategy for combining novel robust (stable) CPs with the Biginelli MCR. In the current manuscript, we describe the synthesis, characterization, photophysical properties and catalytic application of two novel stable and robust zinc-and cadmium-based CPs as the heterogeneous catalysts for the Biginelli reaction, with impressive results under batch and continuous flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, application of sulfonic acid functionalized ionic liquids (ILs) as ''designer solvents'' have attracted considerable attention of chemists due to their unique properties such as high thermal stability, negligible vapor pressure, low flammability, environmental compatibility, reusability, greater selectivity, and ease of isolation [41]. They are known as catalysts or as a dual catalyst-solvent for a wide range of chemical reactions such as Hantzsch, Mannich, Biginelli and Friedlander quinoline synthesis [42][43][44][45]. The above-mentioned advantages encouraged us to explore the new applications of this IL in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%